More Threatened Than Safe: What African, Caribbean, and Black Youth Living In Southern Ontario Say About Their Interactions with Law Enforcement. - Imran Mohamed Syed; Ciann L. Wilson; Raymond McKie; Ashley-Anne Marcotte; Robb Travers (Community Psychology in Global Perspective, 2018)
This study investigates the perspectives of African, Caribbean, and Black (ACB) youth living in Windsor, Ontario regarding their interactions with police. Twelve ACB youth were recruited using various methods through the Promoting and Owning Empowerment and Resilience among African, Caribbean, and Black Youth in Windsor (POWER) project to take part in focus group interviews. Interview transcripts were analyzed using a thematic analysis in NVIVO 10 software. Themes included a belief that police have positive effects on society, and that only a certain minority of officers are responsible for misconduct; many interactions with youth are not the fault of the officer(s) involved and that police institutions play an important role in society. However, youth also expressed reasons for their displeasure with these institutions, such as: the lack of diversity within the police force, and that police sometimes abuse power and can be aggressive. Moreover, police have obstructed justice, profiled, and treated ACB people differently, according to participants. These results come at a time when community advocacy groups, such as Black Lives Matter, are mobilizing to improve the experiences of African diasporic people in Canadian society.